(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the importance of using seismic isolation systems in the design and construction of medical buildings in Uzbekistan, their types, technical requirements, and international experience. It also highlights the role of modern engineering solutions in ensuring the uninterrupted operation of medical institutions during earthquakes.